الاستدلال والتحقيق في جرائم الانترنت في دولة الإمارات العربية المتحدة - Zayed Ali Nasser Algabri; Baidar Mohammed Mohammed Hasan; Syahirah Abdul Shukor (AL-HIKMAH RESEARCH & PUBLICATION CENTRE, 2024)
Vol. 5 No. 2 (2022): MAY ISSUES